Experimental Study of Wind Flow in a Street Canyon between High-Rise Buildings Using PIV - Herlien D. Setio; Prasanti Widyasih Sarli; Yongky Sanjaya; Doni Priambodo (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
In recent years there have been several occasions of failure of non-buildings such as billboard towers and pedestrian bridges around high-rise areas in urban Indonesia. Most cases did not occur during any particular high-speed wind gusts but rather during normal wind speed. This research aimed to show the increase in wind load for structures built between high-rise buildings. A simplified cluster of 4 symmetrical high-rise building was investigated. The study used a wind tunnel and a Particle Image Velocimetry (PIV) device in the experiment. Several angles of attack and also different distances between buildings were investigated to see the impact of these parameters on the wind flow between the buildings. Wind flow experiences an interaction flow in all central areas, which translates into an increase in speed. The change in distance between buildings changes the behavior of the flow in the cross area while a change in the angle of attack of the wind does not influence the amplification factor. The results show that there was an increase from 7 to 44% in wind speed due to the street canyons and that the highest amplification occurred with an angle of attack of 0°.